Microstructural changes and mass transport in cement-based materials: A modeling approach. (January 2021) - Michel, A.; Marcos-Meson, V.; Kunther, W.; Geiker, M.R.
Abstract: A generic modeling framework is presented to relate microstructural changes, i.e. changes in the pore volume distribution and phase assemblage, and mass transport in cement-based materials. The modeling framework accounts for mass transport and chemical equilibrium between ions in the pore solution and solid hydrates by means of an extended version of the Poisson-Nernst-Planck equation, in which the chemical equilibrium is solved by the external geochemical code IPHREEQC. Results of numerical studies concerning carbonation and leaching of a cement-based material indicate significant changes in mass transport properties due to chemical reactions leading to alterations in the microstructure. The resulting highly non-linear (both spatial and temporal) microstructural changes are thereby depending on the exposure and indicate that interactions between chemical reactions, pore structure changes, and mass transport have to be accounted for as a whole. Highlights: Concept to relate microstructural changes, mass transport, and chemical reactions in cement-based materials is presented. Multi-physics modeling approach utilizing an extended version of the PNP equation and the geochemical code IPHREEQC. Case studies indicate significant changes in mass transport properties due to alterations in the microstructure. Microstructural changes depend on exposure and interactions between chemical reactions, pore structure, and mass transport.